2018
DOI: 10.1111/cas.13863
|View full text |Cite
|
Sign up to set email alerts
|

MORC2 promotes development of an aggressive colorectal cancer phenotype through inhibition of NDRG1

Abstract: MORC2 (microrchidia family CW‐type zinc finger 2) is a newly identified chromatin remodeling protein that functions in diverse biological processes including gene transcription. NDRG1 is a metastasis suppressor and a prognostic biomarker for colorectal cancer (CRC). However, the relationship between MORC2 and NDRG1 transcriptional regulation and the roles of MORC2 in CRC remain elusive. Here, we showed that MORC2 downregulated NDRG1 mRNA, protein levels, and promoter activity in CRC cells. We also found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…In CRC, MORC2 has been shown to inhibit N-myc downstream regulated gene 1 (NDRG1), a metastasis suppressor, which promotes cell migration, invasion, and lung metastasis. This study also showed that MORC2 was upregulated in CRC tissues, and high expression was found to be associated with lymph node metastasis [30]. We found that MORC2 levels are higher in plasma samples from patients with lymph node positive CRC, and the findings of these studies together indicate that MORC2 is of interest as a new biomarker, although further studies are needed to elucidate its role in CRC.…”
Section: Discussionsupporting
confidence: 59%
“…In CRC, MORC2 has been shown to inhibit N-myc downstream regulated gene 1 (NDRG1), a metastasis suppressor, which promotes cell migration, invasion, and lung metastasis. This study also showed that MORC2 was upregulated in CRC tissues, and high expression was found to be associated with lymph node metastasis [30]. We found that MORC2 levels are higher in plasma samples from patients with lymph node positive CRC, and the findings of these studies together indicate that MORC2 is of interest as a new biomarker, although further studies are needed to elucidate its role in CRC.…”
Section: Discussionsupporting
confidence: 59%
“…Targeting E2F3 can inhibit the proliferation and induce the apoptosis of colorectal cancer cells and induce the expression of E2F3 to promote the proliferation of colorectal cancer cells [35][36][37][38]. MORC2 is also considered a candidate gene for colon cancer, and previous studies have shown that MORC2 promotes the development of invasive colorectal cancer phenotypes by inhibiting NDRG1 [39][40].…”
Section: Discussionmentioning
confidence: 99%
“…A study has demonstrated that MORC2 expression is notably enhanced in glioma tissues compared with the adjacent tissues, and the higher the level of glioma differentiation, the higher the expression of MORC2 is ( 6 ). Additionally, MORC2 was found to promote the proliferation, invasion and migration of colorectal cancer cells by binding with the promoter region of N-myc downstream regulated gene 1 (NDRG1), a well-characterized metastasis suppressor that has been demonstrated to have the potential to be developed as a target for antimetastatic therapy ( 7 , 8 ). In human cholangiocarcinoma, MORC2 is reported to accelerate the growth and metastasis of cholangiocarcinoma cells via activation of PI3K/Akt signaling ( 9 ).…”
Section: Introductionmentioning
confidence: 99%